El juego libre y creatividad en niños de la Institución Educativa Inicial N° 362 Mi Pequeño Mundo, distrito de Yavarí 2021 - Guedez Falcon, Mari Estel (2024)
The research shows its importance because the results respond to the stated objective of relating free play and creativity in children of the Initial Educational Institution No. 362 My Little World of the Yavarí District. For this purpose, the cross sectional, field and bivariate design was planned, assuming the type of relational research. All the school's students were the population and sample of the study, being 149. The observation technique and two observation guides were applied to collect the respective data. The aforementioned instruments were validated by experts. The conclusion of the study was that the Pearson correlation coefficient (rxy = 0.801) indicates a direct and strong relationship between free play and creativity in children. This value, close to 1, suggests that as free play increases, creativity also increases. The relationship between free play and creativity is not only significant but also positive. This implies that increases in the opportunities and quality of free play are associated with improvements in children's creativity.